SUSTAINABLE SUPPLY CHAIN MANAGEMENT IN MALAYSIA: ISSUES AND FUTURES - Amni Husna Mohd Nashir; Syaimak Abdul Shukor; Aida Sheikhi (Asia-Pacific Journal of Information Technology and Multimedia, 2020)
Sustainable supply chain management is becoming increasingly noticeable and takes place in various industries. It is also applied in the company to improve the performance of the company. However, the standard of sustainable supply chain management is not identical, although in the same industry. Sustainability standards usually focus on service or product management to minimize costs. Most studies focused on a single aspect or two aspects of sustainability, such as on the environment only or focused on the environment and economy only; not many studies focused on all aspects of sustainability. The lack of a common standard that incorporates all three sustainability (environmental, economic, and social) to serve as an essential guide to achieving sustainable supply chain management leads to this study. This paper discussed the overview of supply chain management sustainability in Malaysia. The concept of supply chain management, the sustainability of supply chain management, the importance and relationship between sustainability and supply chain management are thoroughly discussed. The challenges and issues in sustainable supply chain management generally and in Malaysia are also deliberated. Finally, a suitable suggestion for analyzing the sustainability of supply chain management is proposed and concluded.